Analisis Pendapatan Margin Murabahah Pada Koprasi Simpan Pinjam dan Pembiayaan Syari'ah - Abdul Kholik, Daud; Assidiqi, Azmi (Jurnal Etnik: Ekonomi-Teknik, 2021)
This study aims to determine the level of development of murabahah margin income and determine the determination of murabahah financing margins at BMT Tamzis Cimahi Branch. In this study the authors conducted research using descriptive qualitative research methods with a case study approach, namely research conducted in depth about aspects of the social environment including humans in it, either individually, in groups, or in the environment around BMT Tamzis Cimahi branch. The conclusion that can be drawn from this study is that the factors in determining the murabahah margin are based on the ceiling value and financing period and are analyzed using th e 5C + 1S analysis principle including character, capacity, capital, condition, collateral, and sharia and the level of income development in BMT. Tamzis Cimahi branch experienced ups and downs from year to year where it can be seen from 2012 to 2016 the average income was Rp.262,183,200 with a total income of Rp.1,310,916,000 with details in 2013 it decreased by Rp.19,026,000 and decreased again. in 2014 with a total decrease of IDR 184,655,000. however, in 2015 the murabahah contract at BMT Tamzis increased again by Rp. 117,193,000 and in 2016 it increased again from the previous year of Rp. 70,409,000. The determination of the murabahah financing margin at BMT Tamzis undergoes several stages including starting with fundraising, deposit contracts, BMT, financing products, goods and then setting margins to generate income for BMT and 'attayya.